2019
DOI: 10.3389/fphar.2019.01328
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanoparticulate Drug Delivery Approaches for Sublingual and Buccal Administration

Abstract: The sublingual and buccal routes of administration have significant advantages for both local and systemic drug delivery. They have shown to be an effective alternative to the traditional oral route, especially when fast onset of action is required. Drugs can be rapidly and directly absorbed into the systemic circulation via venous drainage to the superior vena cava. Therefore, they are useful for drugs that undergo high hepatic clearance or degradation in the gastrointestinal tract, and for patients that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 70 publications
0
65
0
1
Order By: Relevance
“…The composition and thickness of the oral epithelium depends on the site in the oral cavity. The buccal region refers to the lining of the cheek and has a surface area of ~50 cm 2 [ 82 ]. The buccal epithelium is composed of non-keratinised stratified squamous epithelial cells of around 40–50 cells thick (500–800 μm).…”
Section: Oral Transmucosal Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…The composition and thickness of the oral epithelium depends on the site in the oral cavity. The buccal region refers to the lining of the cheek and has a surface area of ~50 cm 2 [ 82 ]. The buccal epithelium is composed of non-keratinised stratified squamous epithelial cells of around 40–50 cells thick (500–800 μm).…”
Section: Oral Transmucosal Deliverymentioning
confidence: 99%
“…Like other mucosal surfaces, the oral mucosa is coated with a thin layer of mucus which is part of the saliva. The mucus layer, which is 70–100 μm thick, presents a barrier to drug absorption by impeding drug penetration [ 82 ].…”
Section: Oral Transmucosal Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle drug delivery vectors, such as liposomes and polymersomes, have previously been incorporated into electrospun materials for a variety of non-oromucosal applications [ 89 , 90 , 91 ]. Research on oromucosal films containing nanoparticles has shown improvements to absorption and drug solubility and may protect certain drugs from enzymatic degradation [ 92 ]. However, due the additional manufacturing and regulatory complexity, these materials rarely make it to late stage clinical development.…”
Section: Electrospun Mucoadhesive Materialsmentioning
confidence: 99%
“…13 Peak plasma concentration of sublingual formulation (Cmax) is 4 ng/ mL and occurs within 1 hr (Tmax); 11 elimination half-life (t 1/2 ) is 24 hrs (range 13.4 to 39.2 h). [14][15][16] Asenapine is highly bound (95%) to albumin and α 1 -acid glycoprotein. 14 Asenapine has weak affinity to the permeability glycoprotein (P-gp), and so would be unlikely to cause an inordinate increase in prolactin like risperidone, paliperidone, and amisulpride.…”
Section: Pharmacokineticsmentioning
confidence: 99%